Trimester and severity of SARS-CoV-2 infection during pregnancy and risk of hypertensive disorders in pregnancy - Samantha E. Parker; Bhavana Annapragada; Idalis A. Chestnut; Jessica Fuchs; Annette Lee; Vishakha Sabharwal; Elisha M. Wachman; Christina D. Yarrington (Taylor & Francis Group, 2024)
ABSTRACTObjective SARS-CoV-2 infection during pregnancy has been linked with an increased risk of hypertensive disorders of pregnancy (HDP). The aim of this study was to examine how both trimester and severity of SARS-CoV-2 infection impact HDP.Methods We conducted a cohort study of SARS-CoV-2-infected individuals during pregnancy (n = 205) and examined the association between trimester and severity of infection with incidence of HDP using modified Poisson regression models to calculate risk ratios (RR) and 95% confidence intervals (CI). We stratified the analysis of trimester by severity to understand the role of timing of infection among those with similar symptomatology and also examined timing of infection as a continuous variable.Results Compared to a reference cohort from 2018, SARS-CoV-2 infection did not largely increase the risk of HDP (RR: 1.17; CI:0.90, 1.51), but a non-statistically significant higher risk of preeclampsia was observed (RR: 1.33; CI:0.89, 1.98), in our small sample. Among the SARS-CoV-2 cohort, severity was linked with risk of HDP, with infections requiring hospitalization increasing the risk of HDP compared to asymptomatic/mild infections. Trimester of infection was not associated with risk of HDP, but a slight decline in the risk of HDP was observed with later gestational week of infection. Among patients with asymptomatic or mild symptoms, SARS-CoV-2 in the first trimester conferred a higher risk of HDP compared to the third trimester (RR: 1.70; CI:0.77, 3.77), although estimates were imprecise.Conclusion SARS-CoV-2 infection in early pregnancy may increase the risk of HDP compared to infection later in pregnancy.